2017
DOI: 10.1103/physrevb.96.184402
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic perspective on the interplay between electronic and magnetic properties of magnetically doped topological insulators

Abstract: We combine low energy muon spin rotation (LE-µSR) and soft-X-ray angle-resolved photoemission spectroscopy (SX-ARPES) to study the magnetic and electronic properties of magnetically doped topological insulators, (Bi,Sb)2Te3. We find that one achieves a full magnetic volume fraction in samples of (V/Cr)x(Bi,Sb)2−xTe3 at doping levels x 0.16. The observed magnetic transition is not sharp in temperature indicating a gradual magnetic ordering. We find that the evolution of magnetic ordering is consistent with form… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 62 publications
12
28
0
Order By: Relevance
“…While small self-interaction corrections tend to shift the 3d resonances deeper in the VB 13,14,18,21 , this is compensated by the natural charge doping of the host, as we discuss below. Our findings yet support previous resPES results 33,34 , and recent scanning tunnelling microscopy and spectroscopy studies of the electronic fingerprints of substitutional V and Cr impurities in Sb 2 Te 3 18,35,36 . The presence of exchange-split 3d states at E F suscitate the emergence of localised magnetic moments and, possibly, longrange magnetic order.…”
Section: Fingerprint Of the Impurity 3d Statessupporting
confidence: 89%
“…While small self-interaction corrections tend to shift the 3d resonances deeper in the VB 13,14,18,21 , this is compensated by the natural charge doping of the host, as we discuss below. Our findings yet support previous resPES results 33,34 , and recent scanning tunnelling microscopy and spectroscopy studies of the electronic fingerprints of substitutional V and Cr impurities in Sb 2 Te 3 18,35,36 . The presence of exchange-split 3d states at E F suscitate the emergence of localised magnetic moments and, possibly, longrange magnetic order.…”
Section: Fingerprint Of the Impurity 3d Statessupporting
confidence: 89%
“…Fig. 6compiles the experimental results ofKrieger et al (2017) for (Bi,Sb) 2 Te 3 doped with 6% of V, for which the QAH was previously reported(Chang et al 2015). ( a ) shows the V L -edge XAS spectrum, and ( b ) the difference between the on-and off-resonance ARPES intensity at the excitation energies marked in the XAS spectrum as hv B and hv A .…”
supporting
confidence: 83%
“…Despite the early success, dilute magnetic doping has some inherent drawbacks. The dopant atoms occupy either substitutional sites, [ 59–63 ] or interstitial sites [ 60,62 ] (Figure 2b), leading to disorder and degradation of the quality of the crystal, which in turn introduces defect states in the bandgap of the TI, [ 63–65 ] or causes unintentional high doping. [ 66,67 ] Sometimes, these samples are also prone to inhomogeneity issues, [ 68–70 ] which result in microscopic phase separation, and prevent true long‐range ordering of the system.…”
Section: Introductionmentioning
confidence: 99%